Treatment compliance of patients with gastro-intestinal diseases - O. P. Alekseyeva; L. N. Kasimova; Ye. Ye. Goryacheva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2016)
Aim of investigation. To study the effect of some social and psychological factors, disease-related factors, patient-related factors, and also to estimate the effect of psychopathological disorders on treatment compliance in patients with gastrointestinal diseases. Material and methods. Overall 151 patients (57 - with irritable bowel syndrome, 57 - with gastroesophageal reflux disease and 37 - with peptic ulcer of the stomach and duodenum) were investigated by structured interview method applying «the basic questionnaire for clinical and epidemiologic ethnocultural studies». Compliance was estimated by the universal validated Morisky medication adherence scale; the degree of treatment compliance was specified with the help of specially designed questionnaire. Results. At investigation of social and psychological factors it was revealed that most of noncompliant patients were employed (85,9%; p